2006
DOI: 10.1507/endocrj.53.237
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Estrogen-secreting Adrenocortical Carcinoma with Subclinical Cushing's Syndrome

Abstract: Abstract.A 25-year-old man was found to have a large right adrenal mass detected by abdominal echography and computed tomography, and presented with a mild gynecomastia. Endocrine study showed increased serum concentrations and urinary excretion of estrogens and dehydroepiandorosterone sulfate (DHEA-S). The patient had no Cushingoid features but autonomous cortisol secretion, compatible with the diagnosis of subclinical Cushing's syndrome. Surgical removal of the adrenal tumor led to normalization of serum and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 26 publications
1
13
1
Order By: Relevance
“…Cortisol overproduction is often detected in cases with estrogen-producing tumors (17). No hypercortisolemia was observed, although the present case had high levels of 17-OH progesterone, 17-OH pregnenolone and 11deoxycortisol, all precursors of cortisol.…”
Section: Discussioncontrasting
confidence: 52%
See 2 more Smart Citations
“…Cortisol overproduction is often detected in cases with estrogen-producing tumors (17). No hypercortisolemia was observed, although the present case had high levels of 17-OH progesterone, 17-OH pregnenolone and 11deoxycortisol, all precursors of cortisol.…”
Section: Discussioncontrasting
confidence: 52%
“…Previous reports described that a possibility of extra-adrenal aromatization cannot be excluded even though expression of CYP19 was detected in the ACC (22,23). On the other hand, some reports indicated that hypersecretion of estrogen by tumor cells induced feminizing in some ACC cases (17,24,25). Therefore, we think that the cause of the high level of estrogen in the present case was induced by not only an excess production by ACC but also extra-adrenal aromatization.…”
Section: Clinical Manifestationmentioning
confidence: 49%
See 1 more Smart Citation
“…3), while the expression of both CYP17 and CYP11B1 mRNA showed no significant differences between ACC and ACA. The expression of aromatase mRNA increased in only one (Case 1) who showed feminization symptoms [11].…”
Section: Urinary Steroid Excretion Profilementioning
confidence: 95%
“…Two ACC patients (Cases 1, 4) presented with SCS who had suppressed plasma ACTH levels (<5 pg/mL), lack of cortisol diurnal rhythm and its nonsuppressibility of cortisol to high-dose (8mg) dexamethasone suppression test (DST), and one (Case 1) with gynecomastia had high estrogen and DHEA-S levels [11]. Serum DHEA-S levels in ACC were significantly elevated (3137 ±1262 ng/mL) compared to those of ACA (155 ± 44 ng/mL).…”
Section: Urinary Steroid Excretion Profilementioning
confidence: 99%